2006
DOI: 10.1080/00420980600970656
|View full text |Cite
|
Sign up to set email alerts
|

Theorising Power Relationships in Multi-owned Residential Developments: Unpacking the Bundle of Rights

Abstract: This article foregrounds the complex connections between property and law in the multi-owned residential sites which are becoming increasingly common in many countries. Empirical research into intensive housing developments in New Zealand and gated communities in England found that, despite differences in legal structures, individual owners often expressed frustration at their lack of control over the on-going management of such developments. This article suggests an analytical framework for considering and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
114
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(118 citation statements)
references
References 5 publications
(2 reference statements)
4
114
0
Order By: Relevance
“…This model appears to be popular with developers as it provides them with increased flexibility in the way a golf course can be integrated into a development. It is notable that in a study focusing on New Zealand and the UK, Blandy, Dixon, and Dupuis (2006) observed that while there is an apparent passage of property ownership from developer to individual owners in a large strata titled scheme such as an MTGD, the eventual property owners do not enjoy the same scope of influence as owners in conventional property ownership situations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This model appears to be popular with developers as it provides them with increased flexibility in the way a golf course can be integrated into a development. It is notable that in a study focusing on New Zealand and the UK, Blandy, Dixon, and Dupuis (2006) observed that while there is an apparent passage of property ownership from developer to individual owners in a large strata titled scheme such as an MTGD, the eventual property owners do not enjoy the same scope of influence as owners in conventional property ownership situations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This potential for a conflict of interest was only noted late in the course of conducting the interviews and the extent to which it constitutes a challenging issue was not examined in any great detail. For further examination of this issue, see Blandy et al (2006).…”
Section: Interviewee M Commentedmentioning
confidence: 99%
“…Perhaps even more surprising, with the notable exception of Blandy, Dixon and Dupuis' (2006) study, there is a paucity of governance and management enquiries in the broader field of strata titled housing. This signifies that a challenging aspect of this study concerns the identification of an appropriate literary context in which to ground the empirical work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This signifies that a challenging aspect of this study concerns the identification of an appropriate literary context in which to ground the empirical work. Aside from Blandy et al's (2006) study, the two most pertinent literatures identified concern a fledgling literature that focuses on issues arising in tourism based multi titled properties and the generic golf management literature. These literatures form the basis of the review provided here.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ngai-ming and Forrest (2002) highlight the potential for tension to arise between owners with differing levels of wealth and Blandy et al (2006) note conflict of interest issues resulting when a developer attempts to extend a long-term service contract to a building managing agent. A specific MOH scenario was investigated by Guilding and Whiteoak (2008), who examined governance issues arising between accommodation owners and golf club managers in residential golf complexes.…”
Section: Literaturementioning
confidence: 99%